The genetic history of Mayotte and Madagascar cattle breeds mirrors the complex pattern of human exchanges in Western Indian Ocean. Issue 4 (7th February 2022) - Magnier, Jessica; Druet, Tom; Naves, Michel; Ouvrard, Mélissa; Raoul, Solène; Janelle, Jérôme; Moazami-Goudarzi, Katayoun; Lesnoff, Matthieu; Tillard, Emmanuel; Gautier, Mathieu; Flori, Laurence
Abstract: Despite their central economic and cultural role, the origin of cattle populations living in Indian Ocean islands still remains poorly documented. Here, we unravel the demographic and adaptive histories of the extant Zebus from the Mayotte and Madagascar islands using high-density SNP genotyping data. We found that these populations are very closely related and both display a predominant indicine ancestry. They diverged in the 16th century at the arrival of European people who transformed the trade network in the area. Their common ancestral cattle population originates from an admixture between an admixed African zebu population and an Indian zebu that occurred around the 12th century at the time of the earliest contacts between human African populations of the Swahili corridor and Austronesian people from Southeast Asia in Comoros and Madagascar. A steep increase in the estimated population sizes from the beginning of the 16th to the 17th century coincides with the expansion of the cattle trade. By carrying out genome scans for recent selection in the two cattle populations from Mayotte and Madagascar, we identified sets of candidate genes involved in biological functions (cancer, skin structure, and UV-protection, nervous system and behavior, organ development, metabolism, and immune response) broadly representative of the physiological adaptation to tropical conditions. Overall, the origin of the cattle populations from Western Indian Ocean islands mirrors the complex history of human migrations and trade in this area. Abstract : In this study, the authors inferred the demographic history of cattle from Mayotte and Madagascar islands using high-density SNP genotyping data. They found that it closely mirrors the complex pattern of human exchanges in the last centuries in the Western Indian Ocean. They further characterized the adaptive history of the two breeds providing insights into the main adaptive constraints experienced by these two populations since their arrival in the area.